Vitrectomy with intravitreal antibiotic administration in exogenous endophthalmitis treatment in eyes with vision better than light perception - Stopa, Marcin; Kocięcki, Jarosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: to evaluate vitrectomy with intravitreal antibiotic administration in exogenous endophthalmitis treatment in eyes with vision better than light perception. Material and methods: Retrospective review of 9 patients with exogenous endophthalmitis and VA better than light perception. All patients were treated with vitrectomy and intravitreal antibiotic administration. Outcome measures included: preoperative visual acuity and postoperative visual acuity at 6 months, time from the initial ocular surgery and the presentation of endophthalmitis symptoms. Results: Visual acuity at 6 months improved in 88% (8/9), of patients and decreased in 12% (1/9). The mean change in visual acuity was a gain 1.01±0.80 logMAR that corresponds to improvements of 10 lines on ETDRS chart. The differences in mean preoperative and postoperative visual acuity were statistically significant (p=0.009, Wilcoxon signed rank test). No statistically significant differences were detected in mean visual acuity improvement between acute and chronic form of endophthalmitis (p=0.88, Wilcoxon rank sum test). Conclusions: There is more evidence to consider vitrectomy with intravitreal antibiotic administration in eyes with visual acuity better than light perception i.e. in cases that Endophthalmitis Vitrectomy Study (EVS) recommends for intravitreal antibiotic administration alone.